1985
DOI: 10.1016/s0735-1097(85)80336-3
|View full text |Cite
|
Sign up to set email alerts
|

Embolic potential of left ventricular thrombus after myocardial infarction: A two-dimensional echocardiographic study of 119 patients

Abstract: Left ventricular thrombus complicating myocardial infarction was diagnosed by two-dimensional echocardiography in 119 patients. The infarct site was anterior in 98 patients and inferior in 11. Systemic embolism occurred in 26 patients (stroke in 18, lower limb embolism in 7 and mesenteric embolism in 1). A protruding configuration of the thrombus was more common in the patients with embolism than in those without (23 [88%] of 26 versus 17 [18%] of 93) (p less than 0.01). Free mobility of the thrombus was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(85 citation statements)
references
References 17 publications
5
78
0
2
Order By: Relevance
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
supporting
confidence: 83%
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
supporting
confidence: 83%
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
Section: Comment On Guidelines On Oral Anticoagulation With Warfarin4supporting
confidence: 61%
“…Left ventricular thrombi (a frequent complication of transmural acute myocardial infarction, likely to be the case in our patient) 7,8 , are second to atrial thrombi from atrial fibrillation as a cause of cardiogenic embolization. These are easily detectable by two-dimensional echocardiography, although false-positive studies exist 9 .Protruding configuration and free mobility of the thrombus and the presence of adjacent hypokinesia indicate a high embolization potential 10,11 . The presence of a potential embolic source does not, by itself, justify The cause of coronary artery disease in a young patient with a pulseless right arm was further evaluated and was to our surprise a rare entity Takayasu's arteritis.…”
Section: Discussionmentioning
confidence: 99%